Anti-Inflammatory, Antioxidant, and Antifibrotic Effects of Kefir Peptides on Salt-Induced Renal Vascular Damage and Dysfunction in Aged Stroke-Prone Spontaneously Hypertensive Rats - Yu-Hsuan Chen; Hsiao-Ling Chen; Hueng-Chuen Fan; Yu-Tang Tung; Chia-Wen Kuo; Min-Yu Tu; Chuan-Mu Chen (MDPI AG, 2020)
The increased prevalence of renal dysfunction and chronic kidney disease (CKD) and the high costs and poor outcomes of treatment are a significant health issue. The consequence of chronic high blood pressure is the increased prevalence of target organ end-stage renal disease, which has been proven to be a strong independent risk factor for adverse cardiovascular disease. A previous study showed that kefir products have anti-inflammatory and anti-hypertensive activities and immunological modulation functions. However, no data regarding the beneficial effects of kefir peptides (KPs) on salt-induced renal damage or related kidney diseases are available. In this study, KPs were orally administered to aged salt-induced stroke-prone spontaneously hypertensive (SHRSP) rats, and the effects of KPs against inflammation and oxidative stress and their ability to protect against renal dysfunction were evaluated. Fifty-five-week-old SHRSP rats under induction with 1% NaCl in drinking water for 4 weeks showed multiple renal injuries with increased renal inflammation, fibrosis, oxidative stress, tubular atrophy, and glomerulosclerosis. In contrast, oral gavage with KPs reduced the urine protein to creatinine (UPC) ratio, the fractional excretion of electrolytes (FeNa and FeCl), extracellular matrix deposition, and the interstitial fibrotic α-smooth muscle actin (α-SMA) levels in salt-induced SHRSP rats. The renal infiltration of inflammatory cells; the release of monocyte chemoattractant protein-1 (MCP-1), vascular cell adhesion molecule-1 (VCAM-1), endothelin-1 (ET-1), and the cytokine nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 3 (NLRP3) and transforming growth factor-β (TGF-β); the reactive oxygen species (ROS) levels; and histopathological lesions were also decreased in salt-induced SHRSP rats. Furthermore, KP treatment significantly increased the renal superoxide dismutase (SOD) activity and the glomerular filtration rate (GFR), which exerted potent protection against salt-induced chronic kidney disease in SHRSP rats. The results of this study suggest that KPs ameliorate salt-induced renal damage, tubular atrophy, and glomerular dysfunction through anti-inflammatory, antioxidative stress, and antifibrotic activities, and might be a promising protective agent against high salt-induced renovascular-related diseases.